Cretaceous rifting in the geological history of the Ukrainian sector of the Black Sea - Stovba, S.; Fenota, P.; Tyshchenko, А.; Vengrovich, D.; Khriashchevska, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Within the Ukrainian sector of the Black Sea, the Albian-Cenomanian rift faults formed three large rift basins, which consisted of a system of grabens and half-grabens. One of the sublatitude rift basins occupied the modern Karkinit Trough, Krylov-Zmiiny Uplift, Gubkin Ridge and the Sulina Depression on the Odesa Shelf. The second sublatitude basin occupied the modern Tetyaev High, Sorokin Trough, Marine Continuation of the Crimean Folds and, apparently, the Crimean Mountains. The third rift basin extended from the northwest to the southeast and encompassed the Euxinian Graben, Andrusov Ridge, Eastern Black Sea Basin, and Shatskiy High. The greatest depth of the base of the rift sequence is observed in the central part of the Western Black Sea Basin, where it is 15.5–16.5 km. In the Eastern Black Sea basin, the maximum depth is 12.5–13.5 km. The shallowest depths of the base of the rift sequence are characteristic of the Kalamit Swell and the Marine Continuation of the Crimean Folds. During the Cenozoic phases of compression, almost all rift (half)grabens underwent intense folding and vertical movements from several hundreds of meters to 4–5 km. At the same time, most of the rift faults underwent partial or complete inversion.
Keywords: Black Sea; Odesa Shelf; Western Black Sea Basin; Eastern Black Sea Basin; Andrusov Ridge; rifting; rift structures